Data analysis reporting protocols for ground water quality monitoring in the San Luis Valley, Colorado - Goetz, Lacey R., author; Ward, Robert C., advisor; Loftis, Jim, committee member; Cardon, Grant, committee member (Colorado State University. Libraries, 1995)
This thesis investigates the concept of designing a regional, long term, ground water quality information system that complies with all of the laws and regulations applicable and provides information needed by water resource managers, water users, and the general public for the upper, unconfined aquifer in the San Luis Valley, Colorado. A set of “Integrated Information Goals” was developed by Bagenstos (1994) and provides the foundation for this thesis. The laws forming the bases of the information goals are examined further to provide a rationale for translating the information goals into quantifiable statements. These statements are subsequently examined to determine if statistical analysis is required and to develop statistical goals where needed. Statistical methods for handling the data to meet the statistical goals are suggested. Via this exercise, monitoring activities and subsequent data analyses are directly linked to the information goals by the data analysis protocols developed. Reports currently generated that include information about the quality of the water in the upper aquifer of the San Luis Valley are reviewed, along with EPA’s requirements for reporting ground water quality and recommendations for preparing reports presented by the Intergovernmental Task Force on Monitoring. A report format is suggested and samples of graphics for quick and easy conveyance of water quality information sought are provided. This exercise provides the people of the San Luis Valley with a method for ensuring the monitoring system is productive because the final product is defined prior to implementation of the monitoring system. The purpose of this thesis is to demonstrate how to link monitoring activities to legislation, ensuring the accountability of monitoring systems, and providing scientifically defensible information that meets the needs of resource managers and water users.
Keywords: Groundwater -- Quality -- San Luis Valley (Colo. and N.M.); Groundwater -- San Luis Valley (Colo. and N.M.) -- Mathematical models